Methane dry reforming on Ru perovskites, AZrRuO3: Influence of preparation method and substitution of A cation with alkaline earth metals. (March 2019) - Ruocco, Concetta; de Caprariis, Benedetta; Palma, Vincenzo; Petrullo, Antonietta; Ricca, Antonio; Scarsella, Marco; De Filippis, Paolo
Highlights: SrZrRuO3 shows high activity and stability towards dry reforming reaction. Perovskite is very stable, no change in structure are detected after long tests. Catalysts activity is very high notwithstanding the high GHSV employed. Abstract: Dry reforming could become an effective route to mitigate CO2 emission. The process required high temperatures due to its endothermicity and its accompanied by coke formation; therefore, the development of suitable catalysts is fundamental. In this work, ternary perovskites type oxides, AZrRuO3, were synthetized and used in the methane dry reforming. The influences of the preparation method, modified citrate and autocombustion method, and of substitution of the A cation within alkaline earth metals (Ba, Sr and Ca) on the texture, physiochemical characteristics, activity and stability of the catalysts were evaluated. Tests were conducted in a fixed bed bench scale reactor in a temperature range of 600–750 °C. Catalysts synthetized by autocombustion method showed higher reducibility and major surface area and thus better performance in the methane dry reforming. Between them, SrZrRUO3 gave the best results in terms of conversion and stability during long duration tests (66 h). Furthermore, these catalysts showed very good resistance to thermal stresses as demonstrated by XRD analysis performed on used catalysts.